Project Management: A Bibliometric Analysis of Publication Patterns and Research Frontiers (West Science Business and Management, 2026)
This study aims to map the intellectual structure, publication patterns, and emerging research frontiers in project management through a comprehensive bibliometric analysis. Data were collected from the Scopus database and analyzed using VOSviewer to examine co-authorship networks, keyword co-occurrence, and thematic evolution. The results reveal that project management research is anchored by core themes such as decision making, information management, and risk assessment, which form a well-established knowledge base. At the same time, the field is experiencing significant transformation driven by the integration of emerging technologies, particularly artificial intelligence and machine learning, as well as a growing emphasis on sustainability and climate-related issues. The analysis also identifies a distinct yet connected research stream in healthcare and clinical management, highlighting the interdisciplinary application of project management principles. Furthermore, overlay and density visualizations indicate a temporal shift toward more technology-oriented and sustainability-focused topics, reflecting the evolving priorities of both academia and practice. This study contributes to the literature by providing a systematic overview of the development and current trends in project management research, offering insights into future research directions and potential areas for cross-disciplinary integration.